The role of ‘Abang-None’ Jakarta as brand ambassador in enhancing positive image of thousand islands (Research, Society and Development, 2020)
Abang None Jakarta is a pageant event for tourism and culture ambassadors’election in Jakarta. Abang None Jakarta has becoming one of the ways in promoting the tourism sector of a region. The objective of this study is to get information on the efforts of and obstacles faced by Abang None Jakarta as brand ambassador of a thousand islands. The methodology used in this study is descriptive qualitative methodology using two ways communication theory and brand ambassador concept by Khatri. The data are collected using interview, observation and documentation. The result showed that Abang None Jakarta has done their role as a brand ambassador of thousand islands.They had become active informant and giving testimony on thousand islands through social media and word of mouth.